A Sustainable Future with Autonomous Vehicles for Passenger Transport - The Means to Reach a Sustainable Future with Autonomous Vehicles through a Backcasting Approach - Karlsson, Anna; Fredriksson, Emelie (My University, 2019)
Today’s transportation system is associated with a number of negative impacts when it comes to environmental, social, and economic sustainability. A prominent negative impact is the emissions of greenhouse gases from vehicles, contributing to climate change. With new technology like autonomous vehicles (AVs), a potential to transform the way transportation is done today into something more sustainable arises. Car manufacturers are paying more and more attention to AVs and it is likely that this new technology will be diffused into society in the future. The aim of this thesis is to lead the way and show how AVs can be used for passenger transportation in a sustainable manner. The thesis scope is delimited to passenger transport only and the geographical scope is limited to the city of Gothenburg. The contribution of this thesis is to provide an alternative for how to get to a sustainable transportation system in the city of Gothenburg in the future, with the market introduction of AVs. This is done by using a backcasting approach, where a sustainable future scenario, called our desired future, is identified in the first step. Our desired future is based on a robot taxi service, where nobody owns a car. The aim is to reduce resource consumption and to increase the utilization of the existing capacity, by minimizing the number of vehicles and even out the demand for transport. To provide a strategy for how to get to our desired future, gaps between today and the desired future are identified and leverage points for how to bridge the gaps are suggested. This is the first part of the thesis project. In the second part of the project, the gap incentives to not own a car is chosen to focus on. The chosen gap is seen as an important difference between the current situation and our desired future, it is possible to start working with already today, and it is crucial from a sustainability point of view, regardless of how long it will take until fully autonomous vehicles are available on the market. Part 2 aims to find a strategy for how to reduce the need for car ownership, to bridge the chosen gap, which would get us one step closer to our desired future. By using the design thinking methodology, a solution with the aim of decreasing the need for car ownership, called the taxi platform, is developed. The taxi platform gathers the existing taxi companies in an app and enables ride-sharing when beneficial. Hence, the taxi platform is like our desired future, but with drivers instead of AVs. A strategy for how to implement the suggested solution is provided in the form of a business model canvas.
Keywords: Transport; Grundläggande vetenskaper; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Övrig industriell teknik och ekonomi; Transport; Basic Sciences; Sustainable Development; Innovation & Entrepreneurship; Other industrial engineering and economics